An Evaluation of the Effect of Hypnosis on Postoperative Analgesia following Laparoscopic Cholecystectomy. Issue 3 (2nd July 2016) - Joudi, Marjan; Fathi, Mehdi; Izanloo, Azra; Montazeri, Omid; Jangjoo, Ali
Abstract: Little attention has been paid to the effectiveness of hypnosis in improving the results of surgery in Iran. One hundred and twenty patients scheduled for laparoscopic cholecystectomy were randomly divided into either control (standard care) or experimental (hypnosis) groups. Prior to surgery and again after surgery, abdominal pain, nausea, and vomiting were assessed. The results suggest that hypnosis could effectively reduce pain after laparoscopic cholecystectomy and significantly reduce hospitalization time.